2009
DOI: 10.1002/pmic.200800892
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution of native cytosolic proteins of Thermoplasma acidophilum

Abstract: We used molecular sieve chromatography in combination with LC-MS/MS to identify protein complexes that can serve as templates in the template matching procedures of visual proteomics approaches. By this method the sample complexity was lowered sufficiently to identify 464 proteins and - on the basis of size distribution and bioinformatics analysis - 189 of them could be assigned as subunits of macromolecular complexes over the size of 300 kDa. From these we purified six stable complexes of Thermoplasma acidoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…For example, it was reported that Trm56 activity in relation to the formation of pCm56 is clearly detected in cell extract from Pyrococcus furiosus [ 47 ]. Analysis of the T. acidophilum proteome revealed that various proteins form several large (more than 300 kDa) protein complexes and that some protein complexes might interact with the membrane [ 48 ]. Consequently, Trm56 and an unknown tRNA (m 7 G49) methyltransferase might be included in protein complexes and precipitated by centrifugation at 30,000× g .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was reported that Trm56 activity in relation to the formation of pCm56 is clearly detected in cell extract from Pyrococcus furiosus [ 47 ]. Analysis of the T. acidophilum proteome revealed that various proteins form several large (more than 300 kDa) protein complexes and that some protein complexes might interact with the membrane [ 48 ]. Consequently, Trm56 and an unknown tRNA (m 7 G49) methyltransferase might be included in protein complexes and precipitated by centrifugation at 30,000× g .…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, we could not detect Trm56 activity in the crude cell extracts (S-30 and S-100 fractions). Analysis of the T. acidophilum proteome revealed that various proteins form several large (more than 300 kDa) protein complexes and that some of these protein complexes appear to interact with the membrane [ 48 ]. Therefore, T. acidophilum Trm56 might be part of a large complex with other proteins in living cells.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of Thermoplasma extract and purification of endogenous Ta1207. T. acidophilum was cultured aerobically using standard protocols (Robb & Place, 1995) with minor modifications as described previously (Sun et al, 2009). Cells from a 500 ml culture were harvested by centrifugation at 4000g and 4 C for 10 min after 48 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…With 1.5 Mbases, the genome of T. acidophilum was among the smallest at the time of sequencing (Ruepp et al, 2000). Around 35 macromolecular complexes with sizes of greater than 300 kDa were identified in the cytosol of T. acidophilum (Sun et al, 2009). These large complexes are prime candidates for single-particle EM analysis in order to create template libraries for a comprehensive cellular atlas of cellular protein complexes (Nickell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Halobacterium salinarum , 10 of the 14 predicted gas vesicle proteins were identified by LC- MS/MS [32]. Furthermore, molecular sieve chromatography and glycerol gradient ultracentrifugation techniques were paired with MS technology to identify subunits of larger macromolecular complexes in Thermoplasma acidophilum [33;34]. DNA replication machinery of the archaea has also been studied as a dynamic complex in order to identify key elements that exist in common with other domains and those that remain uniquely archaeal.…”
Section: Identification Of Protein Complexes and Networkmentioning
confidence: 99%